2016
DOI: 10.1007/s12035-016-0246-z
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA-N1LR Enhances Neuroprotection Against Ischemic Stroke Probably by Inhibiting p53 Phosphorylation

Abstract: In recent years, long noncoding RNAs (lncRNAs) have been shown to have critical roles in a broad range of cell biological processes. However, the activities of lncRNAs during ischemic stroke remain largely unknown. In this study, we carried out a genome-wide lncRNA microarray analysis in rat brains with ischemia/reperfusion (I/R) injury. The results revealed the differential expression of a subset of lncRNAs. Through the construction of lncRNA-mRNA co-expression networks, we identified lncRNA-N1LR as a novel I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(77 citation statements)
references
References 31 publications
0
76
1
Order By: Relevance
“…Mehta et al exhibited that lncRNA Fos downstream transcript (FosDT) promoted ischemic brain injury by interacting with REST-associated chromatin-modifying proteinsSin3a and coREST [34]. Wu et al found that lncRNA-N1LR promoted neuroprotection against ischemic stroke by inhibiting p53 phosphorylation and served as a potential target for therapeutic intervention following ischemic brain injury [35]. In the present study, we found that MALAT1 was significantly up-regulated in MCAO mice and cortical neurons subjected to OGD, consistent with a previous study [17].…”
Section: Discussionmentioning
confidence: 99%
“…Mehta et al exhibited that lncRNA Fos downstream transcript (FosDT) promoted ischemic brain injury by interacting with REST-associated chromatin-modifying proteinsSin3a and coREST [34]. Wu et al found that lncRNA-N1LR promoted neuroprotection against ischemic stroke by inhibiting p53 phosphorylation and served as a potential target for therapeutic intervention following ischemic brain injury [35]. In the present study, we found that MALAT1 was significantly up-regulated in MCAO mice and cortical neurons subjected to OGD, consistent with a previous study [17].…”
Section: Discussionmentioning
confidence: 99%
“…Dharap performed microarray analysis of rat cerebral cortex and revealed that lncRNA expression profiles are significantly altered after stroke [7]. Wu [8] and Dharap [9] performed microarray analysis of rat brain tissues to identify and explore the potential function of lncRNA-N1LR. Bhattarai performed high-throughput sequencing in rat cerebral cortex and discovered novel stroke-associated lncRNAs [10].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs can suppress precursor mRNA splicing and translation by acting as decoys for RNA-binding proteins or miRNAs, or as competing endogenous RNAs to sponge miRNAs resulting in increased expression of corresponding proteins [18]. Although a series of lncRNAs has been reported to linked to neurodegenerative disorders including Alzheimer’s disease (AD), Parkinson’s disease (PD), and Huntington’s disease (HD), the role of lncRNAs in stroke remains unclear [19, 20]. …”
Section: Introductionmentioning
confidence: 99%